Long non-coding RNA LINC01194 promotes the proliferation, migration and invasion of lung adenocarcinoma cells by targeting miR-641/SETD7 axis - Meng, Fanmei (Cancer Cell Int, 2020)
BACKGROUND: It is increasingly evidenced that long non-coding RNAs (lncRNAs) play an important role in various diseases. LncRNA LINC01194 acts as an oncogene in several cancer types. Nevertheless, the role of LINC01194 in lung adenocarcinoma (LUAD) has not yet been revealed. METHODS: qRT-PCR was used to detect the expression of LINC01194, miR-641 and SETD7 mRNA, while western blot was exploited to examine SETD7 protein level. Cell proliferation was detected by colony formation and EdU assays. Transwell assays detected cell migration and invasion. TUNEL assay and flow cytometry analysis were used to detect cell apoptosis. RIP, RNA pull down and luciferase reporter assays detected the binding among LINC01194, miR-641 and SETD7. RESULTS: LINC01194 was significantly upregulated in LUAD tissues and cell lines. Knockdown of LINC01194 resulted in decreased cell proliferation, migration and invasion, and increased apoptosis. Mechanistic experiments unveiled that LINC01194 augmented SETD7 expression in LUAD cells by competitively interacting with miR-641. Rescue experiments showed that miR-641 inhibition and SETD7 overexpression rescued the repressing impacts on LUAD cell proliferation, migration and invasion caused by LINC01194 knockdown. CONCLUSION: LINC01194 promotes the progression of LUAD by enhancing miR-641-targeted SETD7. The LINC01194/miR-641/SETD7 axis might provide new molecular targets for treating LUAD.